PROBLEMS OF ISLAM AND PHILOSOPHY: ISLAMIC AQIDA AND PHILOSOPHICAL RESEARCH - Zokirova Ra’no Islom qizi (Sciental Journals Publishing, 2025)
This article analyzes the relationship between Islam and philosophy, Islamic aqhids and philosophical studies. The ethical, ontological and epistemological issues present in Islam, as well as their relationship to the development of philosophy and science, are widely covered. The article examines the influence of Islamic philosophy and important stages of its formation, as well as the peculiarities of Islamic thought and philosophical research.
Keywords: Islam, philosophy, aqida, thought, research, ethics, ontology, epistemology, Islamic philosophy